2007
DOI: 10.1371/journal.pbio.0050268
|View full text |Cite
|
Sign up to set email alerts
|

Force-Induced Unfolding of Fibronectin in the Extracellular Matrix of Living Cells

Abstract: Whether mechanically unfolded fibronectin (Fn) is present within native extracellular matrix fibrils is controversial. Fn extensibility under the influence of cell traction forces has been proposed to originate either from the force-induced lengthening of an initially compact, folded quaternary structure as is found in solution (quaternary structure model, where the dimeric arms of Fn cross each other), or from the force-induced unfolding of type III modules (unfolding model). Clarification of this issue is ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
539
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 386 publications
(569 citation statements)
references
References 54 publications
24
539
1
5
Order By: Relevance
“…Circular dichroism spectroscopy of FRET-labeled Fn confirmed that refolding occurs in physiological buffer (Smith et al, 2007).…”
Section: Establishing a Quantitative Fret Vs Strain Curve To Read Oumentioning
confidence: 72%
See 3 more Smart Citations
“…Circular dichroism spectroscopy of FRET-labeled Fn confirmed that refolding occurs in physiological buffer (Smith et al, 2007).…”
Section: Establishing a Quantitative Fret Vs Strain Curve To Read Oumentioning
confidence: 72%
“…Variations of the pulling rate by which the fibers were drawn out of solution, from 1.0 mm/s to 0.2 mm/s, had no major impact on the conformational distribution (data not shown). The width of the histogram originates from the pixel-to-pixel variations of the local averaged Fn conformation and from instrument noise (as further discussed in Smith et al, 2007). The widths of the histograms taken from Fn-d/a in solution (1 M GdnHCl; data not shown) and in manually deposited fibers (Fig.…”
Section: Establishing a Quantitative Fret Vs Strain Curve To Read Oumentioning
confidence: 96%
See 2 more Smart Citations
“…They offer an attractive model for the study of protein aggregation on membranes due to their simplicity compared to cell membranes and their ease of formation on solid supports, making them ideal for use with surface sensitive imaging techniques. Furthermore labeling with donor and acceptor fluorophores allows inter-protein, 29 intra-protein 30 and also protein-lipid interactions 31 to be studied by Förster resonance energy transfer (FRET). Traditional microscopy techniques cannot easily distinguish between fluorescence from surface-bound molecules and background signal from fluorophores in the solution.…”
Section: Introductionmentioning
confidence: 99%